Polythiophene and oligothiophene systems modified by TTF electroactive units for organic electronics - Alexander L. Kanibolotsky; Neil J. Findlay; Peter J. Skabara (Beilstein Journal of Organic Chemistry, 2015)
The aim of this review is to give an update on current progress in the synthesis, properties and applications of thiophene-based conjugated systems bearing tetrathiafulvalene (TTF) units. We focus mostly on the synthesis of poly- and oligothiophenes with TTF moieties fused to the thiophene units of the conjugated backbone either directly or via a dithiin ring. The electrochemical behaviour of these materials and structure–property relationships are discussed. The study is directed towards the development of a new type of organic semiconductors based on these hybrid materials for application in organic field effect transistors and solar cells.